Prediction of the carrier shape effect on particle transport, interaction and deposition in two dry powder inhalers and a mouth-to-G13 human respiratory system: A CFD-DEM study. (February 2022) - Zhao, Jianan; Haghnegahdar, Ahmadreza; Feng, Yu; Patil, Abhijeet; Kulkarni, Nandan; Singh, Gur Jai Pal; Malhotra, Geena; Bharadwaj, Rahul
Abstract: Documentation of comparability between generic inhaler designs and the reference listed drug (RLD) inhalers is essential for regulatory approval of the products. Such assessments need high-fidelity numerical methods to accurately predict the transport, interactions, and deposition of orally inhaled drug products (OIDPs) in the human respiratory systems delivered via inhalers such as dry powder inhalers (DPIs). To explicitly model the particle-particle and particle-wall interactions for OIDPs, this study developed a computational fluid dynamics (CFD) and discrete element method (DEM) to examine drug delivery efficiency, determine emitted aerodynamic particle size distributions (APSDs), and quantify the resultant lung depositions of both lactose carriers and active pharmaceutical ingredient (API) particles. Numerical parametric studies were also performed with multiple actuation flow rates, carrier shapes, and DPI designs. Spiriva™ Handihaler™ (SH) and a generic DPI were selected in this study. The comparability assessment between the generic DPI and SH has been numerically performed. Specifically, CFD-DEM simulations were run at actuation flow rates of 30, 39, 60, and 90 L/min. Simulations were performed for both spherical and elongated lactose carrier particles with aspect ratios of 1, 5, and 10. Using the emitted APSDs as the mouth inlet conditions, the transport and deposition of API and lactose carriers from mouth to the tracheobronchial tree were also simulated. Numerical results indicate that with the same particle volume, the shape of lactose carriers can significantly influence the DPI delivery efficiency without a monotonic trend, due to the complex resuspension effect after deposition. However, the shape effect of lactose carriers is not significant on the lung deposition patterns of the API. Low actuation flow rates could potentially enhance the overall DPI-airway drug delivery efficiency. Using spherical lactose carriers, the comparability between the generic DPI and SH is demonstrated at all four actuation flow rates. The CFD-DEM model provides a feasible pathway on how to use CFD and DEM to evaluate the comparability between inhalers. The modeling framework also can help obtain new insights on transport dynamics of actines in DPIs to lung, thereby reducing the cost of generic product innovations and accelerating product review and approval. Highlights: A CFD-DEM model is developed for simulating particle transport, interaction and deposition in DPIs and human airways. Comparability between two DPIs was assessed based on delivery efficiency, emitted APSDs, and API lung deposition. Shape effect of lactose carriers is significant on particle deposition in DPIs but not significant on API lung deposition. To achieve higher API delivery efficiency in deeper lung, A low actuation flow rate (i.e., 30 L/min) is preferred.